1974
DOI: 10.1111/j.1365-2818.1974.tb03913.x
|View full text |Cite
|
Sign up to set email alerts
|

A cryostat approach to ultrathin ‘dry’ frozen sections for electron microscopy: a morphological and X‐ray analytical study

Abstract: Summary Conventional preparative procedures for the examination of tissues in the electron microscope involve the use of fixatives, dehydration in alcohol or acetone, embedding in plastics and staining. Such procedures remove soluble components and are therefore often unsuitable for chemical analysis of naturally occurring electrolytes. Ultrathin frozen sections of unfixed, unembedded biological tissue can be cut onto dry glass knives, freeze‐dried and viewed in the electron microscope without staining. Morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 11 publications
3
59
0
Order By: Relevance
“…(2) Effects of non-uniform distribution of Na in the oocyte. Crystallization of NaCl during freezing or freeze-drying is not a likely cause of significant nonuniformity since the work of Appleton (1974) suggests that the gaps between such crystals would not exceed 2 Asm so that they would not much affect measurements made in a 3 x 3 4um square, or at least they should affect cell and standard equally; in any case the crystallization of KCI, which presumably occurs, does not appear to affect measurements of K. On the other hand sequestration of non-Li-replaceable Na in the cytoplasm (Dick et al 1970) could give rise to significant non-uniformity in the distribution of at least a part of the oocyte Na. If, for example, 16 m-mole/l.…”
Section: Comparison Of Na Assay By Microprobe Analysis and Flame Photmentioning
confidence: 99%
“…(2) Effects of non-uniform distribution of Na in the oocyte. Crystallization of NaCl during freezing or freeze-drying is not a likely cause of significant nonuniformity since the work of Appleton (1974) suggests that the gaps between such crystals would not exceed 2 Asm so that they would not much affect measurements made in a 3 x 3 4um square, or at least they should affect cell and standard equally; in any case the crystallization of KCI, which presumably occurs, does not appear to affect measurements of K. On the other hand sequestration of non-Li-replaceable Na in the cytoplasm (Dick et al 1970) could give rise to significant non-uniformity in the distribution of at least a part of the oocyte Na. If, for example, 16 m-mole/l.…”
Section: Comparison Of Na Assay By Microprobe Analysis and Flame Photmentioning
confidence: 99%
“…The supercooled Freon 22 was found to yield superior freezing to a liquid N2 slush produced by cooling liquid N2 through vacuum pumping a surrounding container of liquid N2 (boiling point, -196~ freezing point, -210~ as judged by the number of ice crystal-free sections obtained. Preservation of ice crystal-free structures at the electron microscope level requires freezing rates of > 5,000 ~ 10,000~ s. (5,19,23,42,71,77).…”
Section: Tissue Freezing and Cryoultramicrotomymentioning
confidence: 99%
“…The supercooled Freon 22 was found to yield superior freezing to a liquid N2 slush produced by cooling liquid N2 through vacuum pumping a surrounding container of liquid N2 (boiling point, -196~ freezing point, -210~ as judged by the number of ice crystal-free sections obtained. Preservation of ice crystal-free structures at the electron microscope level requires freezing rates of > 5,000 ~ 10,000~ s. (5,19,23,42,71,77).The LKB cryoultramicrotome (LKB Produkter, Bromma, Sweden) was modified so that the ambient temperature in the cryo chamber was -130~ A similar modification was reported while this work was in progress (30). The liquid N2 normally pumped into the knife holder was directed into a large foil trough of about 7 x 3 inches at one end of the chamber.…”
mentioning
confidence: 99%
“…Electron probe analysis combined with cryoultramicrotomy permits the analysis of cell constituents (Z 2 11) with a spatial resolution and sensitivity unavailable through conventional techniques (1,2). It has been shown that it is feasible to detect with commercially available instruments calcium and other cations in single (50-80 nm diameter) mitochondrial granules (3,4).…”
mentioning
confidence: 99%